The Role of Local Elites in Building Social Harmony in Bulutellue Village, Sinjai District - ., Nurlela; ., Jumadi; Rahman, Abdul (KnE Social Sciences, 2024)
This can be proven by the high enthusiasm of the village community in participating in the general elections in 2019. Elections are welcomed with excitement because they will be used as an arena to refresh leadership in both the executive and legislative institutions. People have a great desire to have national leaders who are sincere, committed, and willing to sacrifice in the spirit of nationality. Elections are used as an arena for strengthening democracy that allows power to be operated properly and maximally for the benefit of the general public. However, the very open democratic space also leaves problems in society, namely division due to differences in political choices. Each of them tries and struggles to present their party, presidential and vice presidential candidates as the best. This article will review the efforts of village-level elites in overcoming the phenomenon of division in the community in Bulutellue village as part of the dynamics of the 2019 general election. The method used in this research is the historical method which consists of four stages, namely heuristics, criticism, interpretation, and historiography. The results showed that local elites in Bulutellue village consisting of the village government, businessmen, and religious leaders could overcome community division and realize a harmonious life based on local wisdom, sports, and religious preaching. Keywords: 2019 election, community division, local elite